A Comparison of Risk Factors for Hepatitis C Among Young and Older Adult Prisoners. (October 2014) - van Dooren, Kate; Kinner, Stuart A.; Hellard, Margaret
Internationally, the prevalence of hepatitis C infection is higher among prisoners when compared to the general population, particularly among people who inject drugs. This study estimates the prevalence of, and compares the risk factors for, hepatitis C in young (< 25 years) and older (≥ 25 years) prisoners with a history of injection drug use. Participants were 677 sentenced prisoners in Queensland, Australia, with a lifetime history of injection drug use, recruited in the 6 weeks prior to release from custody. The prevalence of hepatitis C exposure was significantly lower in young prisoners than in older prisoners (20.7% vs. 29.4%, p = .03). Risk factors for hepatitis C varied between young and older prisoners. Young people who inject drugs and who have had shorter time at risk of hepatitis C exposure are an important target group for hepatitis C prevention efforts.